Classical heritage from the epigraphic to the digital : Academia Ragusina 2009 and 2011 - Bratičević, Irena; Radić, Teo; Kurilić, Anamarija; Lučin, Bratislav; Galović, Tomislav; Perić, Olga; Novaković, Darko; Jovanović, Neven, filolog; Tvrtković, Tamara; Rezar, Vladimir; Petrač, Petra; Trachsel, Alexandra; et al. (Ex libris, 2014)
The collection of conference papers Classical heritage from the epigraphic to the digital: Academia Raugisna 2009 & 2011 includes papers from the 2009 and 2011 conferences taking place in Dubrovnik as part of the project supported by Eruopean federation of the national societies of classilac philologists - Euroclassica